Modal Choice Probability Study from Bus to Train At Jombang – Babat Railway Line Reactivation Design - Nugroho Utomo; Fithri Estikhamah (Journal of Civil Engineering Science and Technology (CI-TECH), 2022)
Currently, the transportation mode which connects Jombang City to Babat City in Lamongan Regency on trip is still using bus. This current transportation mode is under appropriated to serving passengers because there are lack of comfortable, unclean, and long headway time approximately 2 – 3 hours for a same routes. Based on these problems, research about intermodal transportation and modal choice probability is suitable. Intermodal transport is designed to revitalize train routes from Jombang to Babat City. A modal choice probability study obtains the number of predicted passengers which can be switched from the existing transportation mode (bus) to the designed transportation mode (train) by using the Stated Preference method. By creating intermodal transportation, obtained train circulation time plan was 303,49 minutes, the headway time plan was 118,6 minutes, the rolling stock plan requirements are three sets of trains and the ticket price plan is IDR 11.500/passenger. According to the difference between train and bus ticket price when the price of train ticket is lower than bus the result of modal choice probability is 0,88. According to the difference between train and bus travel time when train travel time is faster by 42 minutes than bus the result is 0,87. Then due to departure frequency between train and bus when the number of train departures is more thanfive times per day, the probability analysis results is 0,83.